How maternal obesity affects pregnancy? - literature review - Kalicka, Maria; Bielak, Alicja; Gryta, Jakub; Iwan, Karolina; Janczewska, Martyna; Kolasa, Agata; Krysa, Tomasz; Radziejowska, Zuzanna; Szklarz, Magdalena (Quality in Sport, 2023)
Introduction: Obesity is a well-known risk factor for many health problems. Recently, the increasing number of obese pregnant patients deserves our special attention, because maternal obesity is associated with numerous complications during the antepartum, intrapartum, and immediate postpartum stages of pregnancy. Purpose of the study: The aim of this study is to collect and summarize the latest views on maternal obesity in pregnancy and highlights the complications associated with it. Material and methods: Literature review was performed in English different databases, using keywords: morbid obesity, super-obesity, maternal obesity, pregnancy, complications. Results and conclusions: In our systematic review we would like to present the most important threats of obesity among pregnant women such as: cardiovascular, respiratory, endocrinology and gestational weight gain problems; pregnancy loss; fetal anomalies; anesthetic and delivery problems; breastfeeding disorders; problems with contraception and long-distant effects in a child's adult life. Therapeutic success of such a pregnancy should consist of the cooperation of many specialists. This phenomenon of maternal obesity will certainly spread in the future and for this reason - awareness of this problem is very important for both patients and physicians taking care of them.